Estimated Emplacement Temperatures for a Pyroclastic Deposits from the Sundoro Volcano, Indonesia, using Charcoal Reflectance Analyses - Harijoko, Agung; Ayu Safira Mariska, Nanda; Anggara, Ferian (Indonesian Journal on Geoscience, 2018)
DOI: 10.17014/ijog.5.1.1-11This study applies the charcoalification measurement method to infer the emplacement temperature of pyroclastic flow deposits erupted from the Sundoro Volcano, Indonesia. This pyroclastic flow partially covered the Liyangan archeological site, a site where Hindu temples were constructed approximately 1,000 years ago. Five samples of charcoal collected from this area were analyzed for reflectance and elemental composition. Charcoalification temperatures were determined based on mean random optical reflectance values (Ro) plotted on published Ro-Temperature curves. Charcoalification temperatures were also estimated using a published formula based on the charcoal’s hydrogen to carbon (H/C) ratio. These two methods for determining pyroclastic flow deposition temperatures indicated that the pyroclastic deposits that entombed the Liyangan archeological site ranged from 295° to 487°C when they were deposited. This study used very simple, rapid, precise, and low-cost methods of charcoalification temperature measurement to infer the emplacement temperature of a pyroclastic deposit. This estimation procedure could be applied widely to predict emplacement temperatures in volcanic area in Indonesia to enhance volcanic hazard mitigation.